If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2-4x)-3x=65
We move all terms to the left:
2(2-4x)-3x-(65)=0
We add all the numbers together, and all the variables
2(-4x+2)-3x-65=0
We add all the numbers together, and all the variables
-3x+2(-4x+2)-65=0
We multiply parentheses
-3x-8x+4-65=0
We add all the numbers together, and all the variables
-11x-61=0
We move all terms containing x to the left, all other terms to the right
-11x=61
x=61/-11
x=-5+6/11
| -6/13x=-43.5 | | 3v^2+17v+24=5 | | -18=6q | | -1/2(-2x-6)+4=-3x+1/4 | | 6w+3w=72 | | 7d^2-9d+3=5d^2 | | 4w^2+3w-2=-2w | | 5.2n=20.8 | | 4.5s0.5+1=7+4.50, | | 5x=-2x=28 | | 4.5s0.5s+1=7+4.5s0, | | -3=-2x+16 | | 13xˆ2-24x+234=0 | | 2/8-z=24 | | 4n+5=100 | | u+9=-8 | | X+6=5x+2. | | 13x-66=0 | | 4x+7/3x=31 | | 4x+7/3=31 | | p^2-5p+17=4p | | 89+r=134 | | 28x2-25x-42=0 | | 36a^2+35a+6=0 | | -45x2-121x-72=0 | | 49=4x+9 | | 5x+-4=4x+2 | | -24=-8u+4(u+3) | | (x)(x+1)=195 | | a-15=2a-25 | | 4x^-5=75 | | 4/7x=35 |